Hitting the elusive inflation target - Francesco Bianchi; Leonardo Melosi; Matthias Rottner (Deutsche Bundesbank, 2021)
Since the 2001 recession, average core inflation has been below the Federal Reserve's 2% target. This deflationary bias is a predictable consequence of a symmetric monetary policy strategy that fails to recognize the risk of encountering the zero-lower-bound. An asymmetric rule according to which the central bank responds less aggressively to above-target inflation corrects the bias, improves welfare, and reduces the risk of deflationary spirals - a pathological situation in which inflation keeps falling indefinitely. This approach does not entail any history dependence or commitment to overshoot the inflation target and can be implemented with an asymmetric target range. A counterfactual simulation shows that a modest level of asymmetry would have removed the deflationary bias observed in the United States.
Keywords: E31; E52; 330; Asymmetric monetary policy; deflationary bias; deflationary spiral; target range; framework review